Adsorption of heavy metals onto food wastes: a review - Nyairo, Wilfrida; Njewa, Joel B.; Shikuku, Victor O. (Frontiers in Environmental Chemistry, 2025)
There has been an increase in the production of food waste materials worldwide due to rapid population growth. The ineffective and sometimes unscientific and ad hoc disposal of these food waste materials has led to environmental pollution. Studies have reported the occurrence of heavy metals in water resources poses serious health threats to the environment and human health. Heavy metals are documented to be recalcitrant to conventional water treatment facilities since they are non-biodegradable. The use of food waste-based adsorbents provides an alternative solution for the adsorption of heavy metals in water resources, with concomitant benefit of valorization of otherwise waste materials. Therefore, this study examined the applications of food waste-based adsorbents for the removal of heavy metal ions. The study adopted a literature-based approach which involved reviewing published papers from selected science databases. The results indicate that these bioadsorbents have great removal efficiencies for different heavy metals with, rice husks and sugarcane bagasse demonstrating special sorption properties, especially for chromium and lead metal ions, respectively. The adsorption data were mostly best described by the Langmuir and Freundlich isotherm models, suggesting a monolayer coverage with similar sites and a heterogeneous surface, respectively. Further, the kinetic studies indicated that the adsorption processes largely followed a pseudo second-order model, showing chemisorption-mediated rate-limiting steps. However, regardless of these encouraging results attained, the use of food waste-based adsorbents has limitations such as variation in the composition and the structure. This leads to inconsistencies in adsorption efficiencies, regenerations and reuse, and reduced removal capacities. There is also the possibility of leaching of heavy metals from the adsorbents which may in-turn cause secondary pollution. Sustainability investigations such as life cycle assessment, cost-benefit analysis, pilot-scale studies and optimization studies present areas for future research.